The internationalization process of Malaysian SMEs: A case on concerned and tendency towards uncertainty avoidance - Mohtar, Shamimi; Hussain, Fawad (2010)
The main objective of the paper is to aim those factors of uncertainty avoidance which prevent Malaysian SMEs towards internationalization process. The impact of uncertainty avoidance is very high as to know whether Malaysian SMEs are risk takers or not.The human life only differentiates with animals by identifying ethical values among them, and when dealing with different culture around the world it differs in term of how a society deals with international trading electronically. This paper will be looking at how Malaysian SMEs acquire international business while utilizing their risk taking factor on the international business communities.